Analisis Kesehatan Dan Keselamatan Kerja Menggunakan Failure Mode And Effect Analysis Di PT. XYZ - Ramadan, Muhammad; Sukanta, Sukanta; Fitriani, Risma (Jurnal Sistem Teknik Industri, 2021)
Occupational Health and Safety (OHS) is important to maintain and improve so that the quality of human resources in the company is always in prime condition. Every company has a different level or level of Occupational Health and Safety (OHS). PT. XYZ is a company that uses corrosive materials, therefore Occupational Health and Safety (OHS) analyst at PT XYZ is needed. The Occupational Health and Safety (OHS) analysis carried out in this study used the FMEA method to determine which part of the production process had Occupational Health and Safety (OHS) that needed repair the most. From the research results, it was found that the highest Risk Priority Number (RPN) value was the pickling and degreasing production process.